The Experience of Paleoecological Studyof Iron Age Settlements in the Forest-Steppe Fore-Urals - Vladimir V. Ovsyannikov (Археология евразийских степей)
The paper discusses the results of a palynological study of cultural deposits on the monuments of the right bank of the Belaya River in its middle part. Chronologically, the monuments belong to the period from the Late Bronze Age to the High Middle Ages. Representative palynological spectra were obtained from 8 out of the 15 studied sites. The main part of the data relates to the period of existence of the Kara-Abyz culture. Eight stages of vegetation change in the studied region have been identified. The most complete data were obtained for the second to fifth stages, dating back to the period of the IX–II centuries BC. Vegetation changes correlate with climate changes and cultural and historical processes. Based on the conducted research, a conclusion is made about the anthropogenic (human-made) nature of forest-steppe landscapes on the right bank of the middle part of the Belaya River in the Early Iron Age, as well as some shift in the boundaries of vegetation zones in the southern part of the studied area.